Rancang Bangun Sistem Informasi indonesia - Vira Yuanda Harahap Senti Harahap; Ihsan Lubis; Andi Marwan Elhanafi (LKP Unity Academy, 2023)
CV. Medan which is located at Jalan Asia Mega Mas Blok BB No. 6, the second in the city of Yogyakarta. This company has its own product brands, namely Xidol and Eko. This company has many employees so that the performance of the company's employees must be measured properly, measuring employee performance is very important for future evaluation and planning. Evaluation of employee performance absolutely must be done to determine the achievements to be achieved by each employee. If the employee succeeds in achieving the desired target, can create a conducive atmosphere, and can satisfy all parties involved, then the employee can get a proper reward. For this reason, it is necessary to process employee appraisal data which can help make it easier for a superior to make a decision related to selecting an exemplary employee by using the Simple Addtive Weighting (SAW) method in order to be time efficient in selecting exemplary employees.